Identification of an alpha-1 antitrypsin variant with enhanced specificity for factor XIa by phage display, bacterial expression, and combinatorial mutagenesis - Bhakta, Varsha (Sci Rep, 2021)
Coagulation Factor XIa (FXIa) is an emerging target for antithrombotic agent development. The M358R variant of the serpin alpha-1 antitrypsin (AAT) inhibits both FXIa and other proteases. Our aim was to enhance the specificity of AAT M358R for FXIa. We randomized two AAT M358R phage display libraries at reactive centre loop positions P13-P8 and P7-P3 and biopanned them with FXIa. A bacterial expression library randomized at P2′-P3′ was also probed. Resulting novel variants were expressed as recombinant proteins in E. coli and their kinetics of FXIa inhibition determined. The most potent FXIa-inhibitory motifs were: P13-P8, HASTGQ; P7-P3, CLEVE; and P2-P3′, PRSTE (respectively, novel residues bolded). Selectivity for FXIa over thrombin was increased up to 34-fold versus AAT M358R for these single motif variants. Combining CLEVE and PRSTE motifs in AAT-RC increased FXIa selectivity for thrombin, factors XIIa, Xa, activated protein C, and kallikrein by 279-, 143-, 63-, 58-, and 36-fold, respectively, versus AAT M358R. AAT-RC lengthened human plasma clotting times less than AAT M358R. AAT-RC rapidly and selectively inhibits FXIa and is worthy of testing in vivo. AAT specificity can be focused on one target protease by selection in phage and bacterial systems coupled with combinatorial mutagenesis.